Reactions of KBrF4 with platinum metals; Journal of Fluorine Chemistry; Vol. 218 - Ivlev S. I.; Malin A. V. Artem Vladimirovich; Karttunen A. J. Antti; Ostvald R. V. Roman Vyacheslavovich; Kraus F. Florian (2019, 2019)
Title screen